Pengaruh Desain Kemasan Dan Persepsi Kualitas Produk Terhadap Keputusan Pembelian Pada Booth Kopi Nescafe (Studi Kasus Pada Generasi Z Di Tasikmalaya) - Reza Silvia Az Zahra; Ardhiansyah Ardhiansyah (Universitas Dharmawangsa, 2026)
This study aims to analyze the influence of packaging design and product quality perception on purchasing decisions at Nescafé coffee booths among Generation Z in Tasikmalaya. The research is motivated by increasing competition in the instant coffee industry and the decline in Nescafé’s Top Brand Index, indicating changes in consumer preferences. This study uses a quantitative approach with a survey method involving 100 respondents selected through purposive sampling. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination with IBM SPSS. The results indicate that packaging design has a positive and significant effect on purchasing decisions with a significance value of 0.000 < 0.05. Meanwhile, product quality perception does not significantly affect purchasing decisions with a significance value of 0.772 > 0.05. Simultaneously, both variables contribute 63% to purchasing decisions.